Respuesta de un mutante semi-enano de arroz (Oryza sativa L.) a la aplicación de ácido giberelico (ING) - Orozco, Rafael (2000)
In this investigation the effect of giberelic acid (AG3) on the capacity of elongation of the nodes of a semi-dwarf mutant of rice, 2B-95, was studied. The height of this mutant was in the range between 65 and 90 cm and it was obtained by gamma irradiation (Co-60) from a tall variety, WS, with an average height of 165 cm. As an additional control, the semi-dwarf variety CR-1113 was also used. The work was carried out under conditions in vitro applying the AG3 in concentrations of 0,20, 30 and 40 ppm. The answer of the mutant and of the other two genotypes to the exogenous application of the hormone was assessed by measuring the longitude of the sheath of the second leaf emerged after the germination of the seed according to a special modification of the methodology of HARADA and VERGARA (1971). The results indicate that the genotypes WS and CR-1113 were stimulated by all concentrations of AG3, while in the mutant  semi-dwarf 2B-95 the effect was only significant (P<0,05) in the concentrations of 20 and 30 ppm. The concentrations of 40 ppm in this genotype did not activate the genetic system linked with the metabolism of the AG3.